Gout: Diagnosis and management (Faculty of Medicine Universitas Indonesia, 2007)
Goutis a heterogeneous group of diseases resulting from monosodium urate (MSU) crystal deposition in tissues or from supersaturation of uric acid in extracellular fluids. Clinical manifestations include 1) Recurrent attacks of articular and periarticular inflammation, also called gouty arthritis; 2) Accumulation of articular, osseous, soft tissue, and cartilaginous crystalline deposits, called tophi; 3) Uric acid calculi in the urinary tract; and 4) Interstitial nephropathy with renal function impairment, called gouty nephropathy. Gout predominantly is a disease of adult men, with a peak incidence in the fifth decade. In women usually found after menopause.The metabolic disorder underlying gout is hyperuricaemia. The duration and magnitude of hyperuricemia directly correlate with the likelihood of developing gouty arthritis and uric acid urolithiasis, and with age at onset of initial clinical gouty manifestations. The urate crystals induce phagocytes and synovial cells to generate and release such mediators as cyclooxygenase and lipoxygenase metabolites of arachidonic acid, phospholipase A2-activating protein, lysosomal proteases, tumor necrosis factor (TNF)-α, interleukin (IL)-1, IL-6, and IL-8. Definitive diagnosis of gout needs the demonstration of MSU crystals in synovial fluid or tophus. Gout is frequently associated with comorbidity such as obesity, hypertension, renal disease and dyslipidaemia. Therapeutic goals include terminating acute attacks; providing rapid, safe relief of pain and inflammation; averting future attacks; and preventing such complications as formation of tophi, kidney stones, and destructive arthropathy. Colchicine, nonsteroidal anti-inflammatory drugs and corticosteroid are drugs used for treating acute gouty arthritis. Colchicine is also used for prophylaxis. Urate lowering drugs also play a role in prophylactic management of gout. With early intervention, careful monitoring, and patient education, the prognosis is excellent. (Med J Indones 2007; 16:47-54) Keywords: Hyperuricemia, tophus, arthritis, inflammatory mediators, dietary and lifestyle, urate lowering drugs